Association Between Kidney Function and Morphology–Voltage–P Wave Duration (MVP) Score: A Cross-Sectional Electrocardiographic Study - Doğan, Ömer; Ebeoğlu, Abdullah Ömer; Ebeoğlu, Şevval İlke; Acar, Ümit; Barman, Hasan Ali (The European Research Journal, 2026)
Objectives: Chronic kidney disease (CKD) is associated with a high burden of atrial arrhythmias, primarily atrial fibrillation (AF), due to structural and electrical remodelling of the atria. The Morphology–Voltage–P wave duration (MVP) score, a composite electrocardiographic parameter derived from surface electrocardiography (ECG), has been proposed as a simple, non-invasive marker of atrial electrical dysfunction. However, its relationship with renal function has not been previously explored. Methods: This single-centre, retrospective, cross-sectional study included 90 adults with varying levels of estimated glomerular filtration rate (eGFR). MVP scores were calculated from standard 12-lead ECGs, and echocardiographic, demographic, and laboratory variables were recorded. Patients were grouped by eGFR (>60, 30–59, and